2018
DOI: 10.4149/neo_2018_171012n650
|View full text |Cite
|
Sign up to set email alerts
|

Tumor grade as significant prognostic factor in pancreatic cancer: validation of a novel TNMG staging system

Abstract: Aim of the study was to asses the tumor grade prognostic value in the Czech pancreatic cancer patients and to evaluate the accuracy of TNMG prognostic model. Retrospective analysis of 431 pancreatic cancer patients undergoing pancreatic resection in seven Czech oncological centers between 2003 and 2013 was performed. The impact of tumor grade and the accuracy of TNMG prognostic model were evaluated. Lymph node status, tumor size, tumor stage and grade were proved as statistically significant survival predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…In addition, since patients with T4 stage tumors may not be able to undergo surgery, patients with T4 stage pancreatic adenocarcinoma were not included in the study. Consistent with previous findings, the results of the present study demonstrated that, in addition to the T and N stages, tumor grade may also act as an independent predictor for patients with resected pancreatic adenocarcinoma (14,31,37). For example, it has been reported that well-differentiated tumors are significantly associated with longer survival rates (14,37,38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, since patients with T4 stage tumors may not be able to undergo surgery, patients with T4 stage pancreatic adenocarcinoma were not included in the study. Consistent with previous findings, the results of the present study demonstrated that, in addition to the T and N stages, tumor grade may also act as an independent predictor for patients with resected pancreatic adenocarcinoma (14,31,37). For example, it has been reported that well-differentiated tumors are significantly associated with longer survival rates (14,37,38).…”
Section: Discussionsupporting
confidence: 92%
“…The nomogram developed in the present study demonstrated the magnitude of poor prognosis as tumor grade changed from well to poorly differentiated. It has been reported that tumor grade incorporation into the current TNM system enables accurate prognosis prediction within particular clinical stages (30), which has been validated by two subsequent studies (11,37). In the present study, patients with distinct tumor grades were assigned to different points in the nomogram, even if they were classified within the same TNM stage.…”
Section: Discussionmentioning
confidence: 61%
“…We explored the correlation between JAK2 expression, clinicopathological characteristics, and PDAC patient survival in our hospital in this study. Various clinicopathological features including high serum CA19-9 levels and increased tumor size are significantly correlated with poor OS [ 33 , 34 ]. Consistent with previous studies, the present results showed that tumor differentiation and serum CA19-9 levels were associated with OS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the HR of OS increased with the degree of tumor differentiation decreases, and patients who were welldifferentiation suffered better survival than poor-differentiation patients. Several studies also advised that tumor grade should be incorporated into the current TNM classification, because novel TNMG staging system enables more accurate prognosis prediction within particular clinical stages [18,19].…”
Section: Discussionmentioning
confidence: 99%